Managing frame diversity in environmental participatory processes – Example from the Fogera woreda in Ethiopia. (15th July 2016) - Hassenforder, Emeline; Brugnach, Marcela; Cullen, Beth; Ferrand, Nils; Barreteau, Olivier; Daniell, Katherine Anne; Pittock, Jamie
Abstract: Many participatory processes fail to generate social change and collaborative outcomes. This failure can partly be explained by how divergent stakeholders' frames are handled. This paper builds on the framing and participation literature to explain how facilitators can manage frame diversity and foster collaborative outcomes. It suggests two pragmatic steps: identifying frames and managing frames. The two steps are applied to a participatory process for natural resource management in Fogera, Ethiopia. Effectiveness of facilitators' strategies to manage frame diversity in the Fogera case is discussed. Two main elements challenging effectiveness are identified: counter-strategies used by facilitators and most-powerful stakeholders, and the constraining factors knowledge, champions and frame sponsorship. We argue that these elements need to be taken into account by participatory process facilitators when managing frame diversity. Highlights: A diversity of frames can cause participatory processes to fail. We support facilitators in identifying frames and managing frame diversity. Five strategies can be used by facilitators to manage frame diversity. Counter-strategies and constraining factors can hinder strategies' effectiveness. Three factors were identified in Fogera: knowledge, champions and frame sponsorship.